Role of Cilostazol Therapy in Hemodialysis Patients with Asymptomatic Peripheral Arterial Disease: A Retrospective Cohort Study. (22nd September 2016) - Lim, Paik Seong; Jeng, Yachung; Wu, Ming Ying; Pai, Mei-Ann; Wu, Tsai-Kun; Chen, Chang Hsu
Abstract : Background . Peripheral arterial disease (PAD) and its relevant complications are more common in hemodialysis (HD) patients, while the evidence regarding antiplatelet therapy in CKD patients is scarce. We retrospectively analyzed the efficacy of cilostazol on outcomes in HD patients with asymptomatic PAD (aPAD). Methods . This cohort study enrolled 217 HD patients (median follow-up time: 5.75 years). Associations between cilostazol use and the outcomes were evaluated by time-dependent Cox regression analysis. Results . During follow-up, 39.5% (47/119) patients used cilostazol for aPAD and 31.8% (69/217) patients died. Cilostazol users had significantly lower CVD and all-cause mortalities (adjusted HR [95% CI]: 0.11 [0.03, 0.51] and 0.2 [0.08, 0.52]) than nonusers. Both death risks were nonsignificantly higher in cilostazol users than in HD patients without aPAD. The unadjusted and adjusted HR [95% CI] of CVD death risk were 0.4 [0.07, 2.12] and 0.14 [0.02, 0.8] for patients with aPAD during follow-up and were 0.74 [0.16, 3.36] and 0.19 [0.04, 0.93] for those with aPAD at initial. Conclusions . In HD patients with aPAD, lower CVD and all-cause mortality rates were observed in low-dose cilostazol user. Further evidences from large-scale prospective study and randomization trial are desired to confirm the effect of cilostazol.